Methylglyoxal Induced Basophilic Spindle Cells with Podoplanin at the Surface of Peritoneum in Rat Peritoneal Dialysis Model. (3rd May 2015) - Hirahara, Ichiro; Sato, Hideki; Imai, Toshimi; Onishi, Akira; Morishita, Yoshiyuki; Muto, Shigeaki; Kusano, Eiji; Nagata, Daisuke
Abstract : Peritoneal dialysis (PD) is a common treatment for patients with reduced or absent renal function. Long-term PD leads to peritoneal injury with structural changes and functional decline. At worst, peritoneal injury leads to encapsulating peritoneal sclerosis (EPS), which is a serious complication of PD. In order to carry out PD safely, it is important to define the mechanism of progression of peritoneal injury and EPS. We prepared rat models of peritoneal injury by intraperitoneal administration of glucose degradation products, such as methylglyoxal (MGO) or formaldehyde (FA), chlorhexidine gluconate (CG), and talc. In rats treated with MGO, peritoneal fibrous thickening with the appearance of basophilic spindle cells with podoplanin, cytokeratin, and α -smooth muscle actin at the surface of the peritoneum was observed. These cells may have been derived from mesothelial cells by epithelial-to-mesenchymal transition. In FA- or CG-treated rats, the peritoneum was thickened, and mesothelial cells were absent at the surface of the peritoneum. The CG- or MGO-treated rats presented with a so-called abdominal cocoon. In the talc-treated rats, extensive peritoneal adhesion and peritoneal thickening were observed. MGO-induced peritoneal injury model may reflect human histopathology and be suitable to analyze the mechanism of progression of peritoneal injury and EPS.